Assessing reverse remodeling in heart failure patients treated with cardiac resynchronization therapy and its impact on prognosis. (November 2012) - Gabrielli, Luigi; Sitges, Marta; Mont, Lluis
Cardiac resynchronization therapy (CRT) has become an alternative for patients with systolic dysfunction and persistence of heart failure symptoms despite optimal medical therapy. The role of noninvasive cardiac imaging before device implantation still remains controversial, but they are essential to provide an objective evidence of reverse remodeling of the heart which is, in turn, also related to the outcome of patients treated with CRT. The objective of this review is to highlight the acute and long-term CRT benefits as assessed by imaging, with special focus in cardiac reverse remodeling and its impact on prognosis.